Effect of Ta-doping on functional properties of K0.51Na0.49NbO3. (30th August 2019) - Hussain, Fayaz; Khesro, Amir; Muhammad, Raz; Wang, Dawei
Abstract: K.51 Na.49 Nb1−x Tax O3 (0.05 ≤ x ≤ 0.30) ceramics were prepared using a conventional solid-state sintering route. XRD of this system showed the crystal structure shifted gradually from orthorhombic to tetragonal phase. SEM images revealed that grain morphology remained the same in all compounds. At room temperature, relative permittivity has its highest value at x  = 0.20, while tan δ remained less than 5% for all compositions at 100 kHz. For x > 0.05, double peaks were observed in relative permittivity versus temperature data. Saturated and symmetrical ferroelectric loops were obtained at an applied electric field of 60 kV cm −1 . Remanent polarization (Pr ) decreased with increasing x, however coercive field (Ec ) was almost independent of composition. Isovalent doping of Ta 5+ ( T a N b x ) marginally improved d33 at low concentrations (i.e., maximum d33  = 135pC/N, at x = 0.10). However, the broadening of peaks observed in dielectric data due to inhomogeneity may open new applications in microwave dielectrics or relaxor type applications in smart ceramics.